ANALYSIS OF THE EFFECTIVENESS OF ARGUMENTATION LEARNING MODELS FOR INCREASING STUDENTS ARGUMENTATION SKILLS BASED ON SCORING MATRIX LEVELS OF TOULMINS ARGUMENTATION PATTERN (TAP) IN PHYSICS LEARNING - RIZKI RAHMAN, NIZAR; ADMOKO, SETYO (Inovasi Pendidikan Fisika, 2020)
This study aims to determine the effectiveness of learning models in improving students argumentation skills. This effectiveness is in the form of increasing the level of argumentation of students from before applying the learning model until after the learning model is applied. The type of research used is library research, that is research in which data or research objects are obtained through various library information such as journals, books, encyclopedias, and similar literature. The data source used by this research is secondary data. This research data analysis method is a descriptive analysis method, which is the decomposition of data obtained regularly and then given an understanding and explanation so that the reader can understand the contents of the data obtained properly. Based on the results of the study, it was found that the average argumentation skill of students using the scoring matrix Toulmins Argumentation Pattern before applying the learning model was at level 1-2. After applying learning and re-measuring the skill of argumentation shows level 3-4 although in one learning model still shows level 2. Two learning models are best to be applied to improving students argumentation skills. First the inquiry model with the Argument Based Science Inquiry (ABSI) learning model with an increase of 2 levels after learning is applied with a high n-gain value category. Second, Argument-Driven Inquiry (ADI) with an increase of 2 levels after applying learning with a moderate n-gain value category. Both of these models can improve students argumentation skill to level 4 where after learning the students can formulate arguments accompanied by a conditional rebuttal and the rebuttal begins to be seen.